Impact of the Moralba Science and Technology Seminar on the strengthening of concepts in Science, Mathematics and Technology - Gallego Joya, Leonardo (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2024)
The Moralba Science and Technology Seedbed in the southeastern Moralba school has proven to be an influential educational project that seeks to strengthen concepts of science, technology and mathematics for elementary, high school and middle school students through the STEM strategy. In the technological field, it highlights the importance of the RobótiKa Moralba project and the center of interest in Robotics, where they get involved in teams linked to STEM Olympics and programming with Arduino, which provides them with the valuable opportunity to apply theoretical knowledge in the realization of concrete projects. In the scientific field, it incorporates the Antares club and the Astronomy interest center, both designed to carry out theoretical-practical activities related to astronomy. This approach contributes to the strengthening of curricular knowledge in natural sciences and mathematics, promoting the scientific abstraction necessary for a deep understanding of the topics in this field. These activities not only stimulate curiosity and passion for science, but also create an enriching educational environment that integrates technological and scientific aspects. In the case of students, it encourages their participation in hands-on projects, olympiads and astronomy-focused activities, developing meaningful skills in science and technology. This integrated approach aims to prepare students for future challenges and opportunities. This aspect allows the seedbed to be a catalyst for the strengthening of STEM concepts, providing students with the tools and interest necessary to excel in these disciplines.